Meat and heterocyclic amine intake, smoking, NAT1 and NAT2 polymorphisms, and colorectal cancer risk in the multiethnic cohort study - Nöthlings, Ute; Yamamoto, Jennifer F; Wilkens, Lynne R; Murphy, Suzanne P; Park, Song-Yi; Henderson, Brian E; Kolonel, Laurence N; Le Marchand, Loïc (Cancer epidemiology, biomarkers & prevention, 2009)
N-acetyltransferases (NAT) 1 and 2 are polymorphic enzymes catalyzing the metabolic activation of heterocyclic amines. We investigated the modifying effects of NAT1 and NAT2 polymorphisms on the association of meat consumption, heterocyclic amine intake, and smoking with colorectal cancer risk. In the Multiethnic Cohort study, participants completed a smoking history and a food-frequency questionnaire at recruitment and a cooked meat module 5 years later to estimate heterocyclic amine intake (2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine, 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline, 2-amino-3,4,8-trimethylimidazo[4,5-f]quinoxaline). Blood samples were collected from incident cases and age-, sex-, ethnicity-, frequency-matched controls to determine genotypes. For analysis of meat intake and smoking, data were available for 1,009 cases and 1,522 controls; for heterocyclic amine intake analyses, 398 cases and 1,444 controls were available. Multivariate logistic regression models were used to estimate odds ratios. Smoking was associated with an increased colorectal cancer risk (odds ratio, 1.51; 95% confidence interval, 1.17-1.95) for > or =30 pack-years compared with never smokers (P trend = 0.0004). The association was stronger with presence of the "rapid" compared with the "slow/intermediate" NAT2 genotype (P interaction = 0.003). No significant associations were observed for intakes of red meat, processed meat, and heterocyclic amine, or meat doneness preference, but a dietary pattern high in meat showed a weak positive interaction with the NAT2 genotype (P interaction = 0.05). The enhanced association between smoking and colorectal cancer risk in subjects with the NAT2 rapid genotype supports a role for NAT2 and tobacco smoke heterocyclic amines in the etiology of colorectal cancer. This study only provides weak support for a similar association with meat heterocyclic amines.